An EMG-driven biomechanical model of the canine cervical spine. (February 2017) - Alizadeh, M.; Knapik, G.G.; Dufour, J.S.; Zindl, C.; Allen, M.J.; Bertran, J.; Fitzpatrick, N.; Marras, W.S.
Abstract: Due to the frequency of cervical spine injuries in canines, the purpose of this effort was to develop an EMG-driven dynamic model of the canine cervical spine to assess a biomechanical understanding that enables one to investigate the risk of neck disorders. A canine subject was recruited in this investigation in order to collect subject specific data. Reflective markers and a motion capture system were used for kinematic measurement; surface electrodes were used to record electromyography signals, and with the aid of force plate kinetics were recorded. A 3D model of the canine subject was reconstructed from an MRI dataset. Muscles lines of action were defined through a new technique with the aid of 3D white light scanner. The model performed well with a 0.73 weighted R 2 value in all three planes. The weighted average absolute error of the predicted moment was less than 10% of the external moment. The proposed model is a canine specific forward-dynamics model that precisely tracks the canine subject head and neck motion, calculates the muscle force generated from the twelve major moment producing muscles, and estimates resulting loads on specific spinal tissues.